Introducing Retro Products In The Sports Industry With Augmented Reality Applications - YORULMAZLAR, MEHMET MUSTAFA (LAHORE MEDICAL RESEARCH CENTER LLP, 2021)
The sports industry has caused differentiation in marketing strategies with the effect of globalization. As a result of this differentiation, manufacturers have put the demands of their customers at the center of production. In the study; It is aimed to reveal the interaction elements within the scope of the retro marketing application area activities in the promotional videos of the Nike brand to impress people. The sample of the study consists of 4 promotional videos: Nike Air Max 2090 Cloud, Explore Air Force I City, Build Your Nike Air Max 2090, Nike Air Max 720 Day, featuring augmented reality technology with the retro products of the Nike brand. Density sampling method was used while determining the sample. Density sampling covers the best or most information-rich examples of the investigated phenomenon, rather than extreme or unusual cases. Basic Qualitative Research Model was applied as a research method. The main purpose of basic qualitative research is to reveal and interpret the meanings created by people. As a pattern in the study; document analysis technique was used. Documents used in qualitative research consist of four types: Public records and personal documents are the first and second types, popular culture documents are the third type, and visual documents including movies, videos, and pictures are the fourth type. This study consists of videos in the visual documents section of the fourth type. Analysis of the data obtained in our study; It was carried out according to 5 main titles and 10 sub-titles within the framework of Retro Marketing Application Area in Sports As a result; The Nike brand used augmented reality technology to present its products with a combination of old and new features to its consumers within the framework of retro marketing and to enable them to establish an emotional connection with the past. Under the title of images of the retro marketing application field in sports; It was observed that the redesign of AirMax and Air Force shoe models, which are identified with the brand and the titles of giveaways and themed games/events were emphasized in game day promotions.
Keywords: Sports Industry; Communication; Retro Marketing; Augmented Reality; Promotion